A Case-Control Study of Correlates of Severe Acute Maternal Morbidity in Kabul, Afghanistan - Todd, Catherine S. (Int J Gynaecol Obstet, 2015)
OBJECTIVE: To identify correlates of severe acute maternal morbidity (SAMM) in Kabul, Afghanistan. METHOD: Case-control study enrolled postpartum couples between 2007 and 2009. Case eligibility was determined by SAMM criteria abstracted from medical records and husband consent; controls (uncomplicated deliveries) were matched by age, parity, and interval from last delivery. Interviews queried sociodemographics, medical history, care access, and index pregnancy perceptions. SAMM correlates were analyzed with conditional logistic regression in models including (proximate) and excluding (distal) care factors. RESULTS: Among 285 matched couples, most frequent SAMM diagnoses were obstructed labor (104 (36.5%)) and hemorrhage requiring transfusion (102 (35.8%)). In distal and proximate models, SAMM was associated with >1 wife (Adjusted Odds Ratio (AOR)=48.6, 95% Confidence Interval (CI): 5.4 - 436.5 and AOR= 418, 95% CI: 3.5 - 5819, respectively) and prior stillbirth (AOR=16.2, 95% CI: 6.1 - 42.9, and AOR=8.0, 95% CI: 2.9 - 22.4, respectively). Visiting another facility before hospitalization (AOR=7.5, 95% CI:3.1 - 17.9), planned home delivery (AOR=5.5, 95% CI: 1.5 - 20.0), and provider-determined care-seeking (AOR=4.8, 95% CI: 1.6 - 14.9) were associated in proximate models. CONCLUSION: Planned home delivery and referral to multiple facilities or by providers are SAMM-associated factors potentially amenable to intervention in Afghanistan.